RUSSIAN EMBASSY CHURCHES AND PRIEST DURING THE REIGN OF NICHOLAS I - E. P. Koudryavtseva (Vestnik MGIMO-Universiteta)
The article is devoted to activity of orthodox priests in Russian embassies and missions. All Russian embassies in Europe had churches and family chapels with the personnel. They submitted to ambassadors or heads of Russian missions, were accountable to the Russian Foreign Ministry that paid them salary. Most of the Holy Synod also controlled them. During the reign of Nicholas I the priests were appointed to those eastern countries with whom Russia wanted to open up diplomatic relations. The greatest number of cleric was in the Ottoman Empire and Greece. Churches and church services in these countries had to be examples for orthodox communities for the Balkan Slavic population where orthodox church services are usually non-canonical. Special attention should be paid to the Russian Orthodox Ecclesiastical Mission in China that also served as a diplomatic mission there. During the second quarter several Orthodox Ecclesiastical Mission were established in China and remained there for a long time, while Russia still had no diplomatic relations with China. The article is based on documents from the Archive of foreign policy of Russian Empire that have never been engaged in scientific researches. The theme of clerics’ membership in Russian embassies has never been studied before (except for few works concerning Russian clergy in the Holy Land). The large scale of materials that shows an important role of embassy clerics make it possible to significantly broaden the study of the activity of the Russian representational offices.